2016
DOI: 10.1016/j.ccell.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Transmitted lncARSR Promotes Sunitinib Resistance in Renal Cancer by Acting as a Competing Endogenous RNA

Abstract: Sunitinib resistance is a major challenge for advanced renal cell carcinoma (RCC). Understanding the underlying mechanisms and developing effective strategies against sunitinib resistance are highly desired in the clinic. Here we identified an lncRNA, named lncARSR (lncRNA Activated in RCC with Sunitinib Resistance), which correlated with clinically poor sunitinib response. lncARSR promoted sunitinib resistance via competitively binding miR-34/miR-449 to facilitate AXL and c-MET expression in RCC cells. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
768
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(807 citation statements)
references
References 44 publications
9
768
0
7
Order By: Relevance
“…Numerous studies have reported that lncRNAs could be crucial players in cancer progression, particularly in terms of dysregulation of gene products that contribute to advanced human tumors [5][6][7]. Furthermore, lncRNAs could also be considered as diagnostic or prognostic markers due to their clinical association with tumor outcomes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that lncRNAs could be crucial players in cancer progression, particularly in terms of dysregulation of gene products that contribute to advanced human tumors [5][6][7]. Furthermore, lncRNAs could also be considered as diagnostic or prognostic markers due to their clinical association with tumor outcomes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Linc00974 interacting with KRT19 promoted proliferation and metastasis by acting as a sponge of miR-642 in hepatocellular carcinoma [12]. Moreover, lncARSR was transmitted by exosomes and promoted sunitinib resistance in renal cancer [13]. Functional studies have confirmed that many lncRNAs are involved in the development and progression of NSCLC [14], including HOTAIR, H19, CCAT2, and AGAP1-AS1, acting as cancer-promoting genes, and MEG3, LET, GAS5-AS1, and TUG1, behaving as tumor suppressors [15-22].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a number of studies reported that mRNA, miRNAs, and long non-coding RNAs are secreted from different types of cells through extracellular vesicles (EVs) [15] and play important roles in cell-to-cell communications such as inflammatory response, tissue regeneration, and tumor progression [16][17][18][19][20].…”
Section: Secretion Of Mirnasmentioning
confidence: 99%